Hidden Threats in Words: Forensic Linguistic Patterns of Child Sexual Violence Perpetrators in Merauke - Diliana, Ekfindar; Goncalves Klau, Ricardo; Tarigan, Dina Mariana Br; Santo, Zem; Retnaningtyas, Hanova Rani Eka (Lembaga Teewan Journal Solutions, 2026)
This study aims to (1) identify the language patterns used by perpetrators of child sexual violence, (2) analyze manipulation and intimidation strategies embedded in their speech, (3) explain the role of language as a tool of psychological control, and (4) examine the influence of local socio-cultural factors on the perpetrators’ discourse in Merauke. The research data were collected from Examination Minutes (BAP), recorded conversations, and supporting legal documents related to child sexual violence cases. The study applies Critical Discourse Analysis, ethnography of communication, and forensic linguistics approaches to reveal how perpetrators construct power relations, create fear and guilt, and exploit local cultural norms to dominate child victims. The findings indicate that perpetrators employed systematic linguistic patterns, including promises of gifts, deceptive expressions of affection, persuasive commands, and indirect threats to manipulate and intimidate victims. These strategies effectively influenced the victims’ emotions, behavior, and decision-making processes. The manipulation was further strengthened by local communication practices that emphasized respect for elders and obedience to adult authority. The novelty of this study lies in its forensic linguistic analysis of perpetrators’ language in child sexual violence cases in Merauke, South Papua. The findings demonstrate the value of linguistic evidence for legal investigations and child protection efforts.